The Importance of Zakat as a Booster for the Community's Economy - Kahar Muzakir (PT FORMOSA CENDEKIA GLOBAL, 2023)
Strengthening the community's economy using the zakat scheme is one of the best ways to improve the community's economy after the Covid 19 pandemic. Zakat is one of the pillars of Islam which has dimensions of worship and muamalah. Paying zakat is an obligation of worship which is a consequence of obedience to the commands of Allah SWT, and its use can help solve economic problems (muamalah) faced by the state, especially society, especially the problem that is often faced by a country and is very difficult to solve is the problem of poverty. These problems can be solved by making fundamental and comprehensive changes with the perfect implementation of sharia law; including the collection and distribution of zakat in accordance with predetermined provisions. With the majority being Muslim, it is believed that society must participate in issuing zakat. However, we cannot deny that there are still many ordinary people who are even reluctant to pay zakat. very big because if so far the obligation of zakat is only in name. Therefore, to anticipate it, community participation is needed, especially community participation in issuing zakat